Benralizumab Prevents Recurrent Exacerbations in Patients with Chronic Obstructive Pulmonary Disease: A Post Hoc Analysis - Dave Singh; Gerard J. Criner; Àlvar Agustí; Mona Bafadhel; Johan Söderström; Gabriela Luporini Saraiva; Yue Song; Idlir Licaj; Maria Jison; Ubaldo J. Martin; Ioannis Psallidas (2023)
Exacerbations in chronic obstructive pulmonary disease (COPD), which tend to occur in clusters and increase with disease severity, come with high societal and economic burdens. Prevention and delay of recurrent exacerbations is an unmet and significant therapeutic need for patients with COPD. GALATHEA (NCT02138916) and TERRANOVA (NCT02155660) were trials assessing efficacy of benralizumab in patients with frequent COPD exacerbations despite treatment. Although these studies found that benralizumab given as an add-on treatment did not significantly reduce annual rates of COPD exacerbations after 56 weeks of treatment, in the following exploratory post hoc analysis of the GALATHEA and TERRANOVA trials we identified a potential responder population in which treatment with benralizumab prevents recurrent COPD exacerbations during 30- and 90-day periods following an initial exacerbation, a vulnerable period for an exacerbation to occur. This responder population was characterized by high blood eosinophil counts and frequent previous exacerbations despite optimized triple therapy. These results highlight the importance of targeted therapies for high-risk populations and merit further research into the benefits of biologic therapies for COPD exacerbations.